Response of Lycopersicum esculentum Mill to different Arbuscular Mycorrhizal fungi species - Tahat, M. M; Sijam, Kamaruzaman; Othman, Radziah; Kadir, Jugah; Masdek, H. N (Asian Network for Scientific Information, 2008)
The ability of endomycorrhizal fungi to colonize tomato (Lycopersicum esculentum. Mill) roots, was studied under glasshouse conditions. Two indigenous species; Glomus mosseae and Scutellospora sp. and non-indigenous species Gigaspora margarita were used in the study. Pot culture technique was used for re-culturing G. mosseae and Scutellospora sp., sorghum was used as a trap host. Gigaspora margarita was re-cultured by test tube technique. All species had the ability to colonize tomato root with different colonization levels. Significantly higher root were colonized by G. mosseae (80%) compared to G. margarita (20%). A G. mosseae significantly increased shoot dry weight (2.82 g) and flowers number (32.75 g) and root growth. Tomato plants treated by G. mosseae were higher significantly after seven week of plant growth. The colonization of tomato root by G. mosseae lead to bigger root size and more branching which increase positively the number of root tips, length, surface area and root volume. Higher spores (455/100 g) were counted in Glomus mosseae inoculated plant compared to Scutellospora sp. (250/100 g) and G. margarita plant (132/100 g).